2015
DOI: 10.1017/ice.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in All Healthcare-Associated Infections through Comprehensive Hospital-wide Surveillance and Infection Control Measures over the Past 12 Years: Substantial Burden of Healthcare-Associated Infections Outside of Intensive Care Units and “Other” Types of Infection

Abstract: We demonstrated success in reducing overall HAIs over a 12-year period. Our data underscore the necessity for surveillance and infection prevention interventions outside of the ICUs, for non-device-associated HAIs, and for CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
2
18
2
Order By: Relevance
“…1 A smaller study in Denmark reported a rate of 6.4 per 10,000 patient days and another in the United States reported a range between 11.2 and 6.7 per 10,000 patient days. 2,3 The HABSI rates were consistently higher in teaching hospitals and often higher in nonteaching hospitals with ICUs compared to nonteaching hospitals without ICUs. It is common for HAI rates to be higher in teaching hospitals because they often receive sicker patients given their mission to provide specialized care for severely ill patients who are more vulnerable to HABSI.…”
Section: Discussionmentioning
confidence: 99%
“…1 A smaller study in Denmark reported a rate of 6.4 per 10,000 patient days and another in the United States reported a range between 11.2 and 6.7 per 10,000 patient days. 2,3 The HABSI rates were consistently higher in teaching hospitals and often higher in nonteaching hospitals with ICUs compared to nonteaching hospitals without ICUs. It is common for HAI rates to be higher in teaching hospitals because they often receive sicker patients given their mission to provide specialized care for severely ill patients who are more vulnerable to HABSI.…”
Section: Discussionmentioning
confidence: 99%
“…HAIs were identified through the UNC Hospitals' Epidemiology database, which included both device and non-device-associated HAIs, captured through comprehensive, hospital-wide active surveillance, in accordance with CDC case definitions and methodology. 7,15 In July 2014, the UNC Hospital Department of Epidemiology began also capturing ventilator-associated events, a new surveillance concept that CDC developed as an alternative to traditional VAP surveillance. 16 The 2 databases were then deterministically linked using admission date, medical record numbers, and full name.…”
mentioning
confidence: 99%
“…HAIs were identified through the UNC Hospitals' Infection Prevention database, which included both deviceassociated and non-device-associated HAIs captured through comprehensive, hospital-wide active surveillance in accordance with the Centers for Disease Control and Prevention (CDC) case definitions and methodology. 11,13 The CDC definition of UTI (device and non-device associated) require the patient has at least 1 sign or symptom (eg, fever, suprapubic tenderness, urinary frequency, and/or urinary urgency) and a urine culture with a bacterium of either ≥10 3 CFU/mL (2013-2014 definition) or ≥10 5 CFU/mL (2015-2017 definition). All diagnoses were reviewed and validated by 2 independent reviewers.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%